A Polyvalent Peptide CD40 Nanoagonist for Targeted Modulation of Dendritic Cells and Amplified Cancer Immunotherapy. Issue 24 (12th May 2022) - Mamuti, Muhetaerjiang; Wang, Yi; Zhao, Yong‐Dan; Wang, Jia‐Qi; Wang, Jie; Fan, Yan‐Lei; Xiao, Wu‐Yi; Hou, Da‐Yong; Yang, Jia; Zheng, Rui; An, Hong‐Wei; Wang, Hao
Abstract: Targeted immunomodulation through biomolecule‐based nanostructures, especially to dendritic cells (DCs), holds great promise for effective cancer therapy. However, construction of high‐performance agonist by mimicking natural ligand to activate immune cell signaling is a great challenge so far. Here, a peptide‐based nanoagonist toward CD40 (PVA‐CD40) with preorganized interfacial topological structure that activates lymph node DCs efficiently and persistently, achieving amplified immune therapeutic efficacy is described. The on‐site fabrication of PVA‐CD40 is realized through the click conjugation of two functional peptides including the "CD40 anchoring arm" and the "assembly‐driving motor." The resultant polyvalent interface rapidly triggers the receptor oligomerization and downstream signaling. Strikingly, one shot administration of PVA‐CD40 elicits maturation period of DCs up to 2.3‐fold comparing to that of CD40 antibody. Finally, combining the PVA‐CD40 with anti‐PD‐1 antibody results in subsequent inhibition of tumor growth in both B16F10 and 4T1 mice tumor models with survival rate up to 37%, while none of the mice survives in the clinically relevant CD40 mAb and anti‐PD‐1 combination‐treated group. It is envisioned that the fabrication of antibody‐like superstructures in vivo provides an efficient platform for modulating the duration of immune response to achieve optimal therapeutic efficacy. Abstract : Superstructural nanoagonist (PVA‐CD40) with preorganized interfacial topological structure is constructed through click reaction directed in vivo self‐assembly. PVA‐CD40 is able to drain and retain in lymph node to induce sustained dendritic cells maturation through CD40 signaling and further leads to durable CD8 + T cell output for tumor regression and rejunction of tumor metastasis.